Perlindungan Hukum Tenaga Kerja Indonesia (TKI) Yang Melebihi Batas Masa Tinggal (Overstay) - Lalu Adhi Adha (Fakultas Hukum Universitas Mataram, 2015)
Along with the increasing migrant workers abroad, many of them going on violations committed by migrant workers, such as migrant workers exceeded the limit of stay (overstayed), with the position of migrant workers overstayed thus vulnerable to violations of the rights of migrant workers and abuse, because with these positions is considered more beneficial for the users of services of migrant workers / employers to hire migrant workers and do anything improper, such as paying low wages, hours of work beyond normal working hours and so on, hence the need for protection in order to fulfill the fundamental rights of migrant workers is concerned. Therefore the issue of how the legal protection of Indonesian workers that exceed the limit of stay (overstayed) and how the responsibilities of service users migrant workers / employers against workers who exceed the limit of stay (overstayed) be an interesting issue to be discussed. This paper is the result of normative legal research that examines the issues, based on the literature and legislation relating to the problems examined. Therefore, the approach used that approach to law (Statute Approach) and Conceptual Approach (conceptual approach). Based on the research that the protection of workers who exceed the limit of stay (overstayed) is not strictly regulated by Law No. 39 Year 2004 concerning the Placement and Protection of Indonesian Migrant Workers Abroad and implementing regulations, but overstayed the problem is a problem during the placement of migrant workers abroad, the protection refers to the period of placement that is as described in Article 17 to Article 23 PP. No. 3 In 2013 on the Protection of Migrant Workers Abroad in the form of guidance and supervision, assistance and consular protection, the provision of legal aid, defense and fulfillment of the rights of migrant workers, diplomatic efforts and so on, as well as in Law No. 6 Year 2012 on the Ratification of the International Convention on the Protection of All Workers and Members of Their Families also ensure the protection of migrant workers as well to TKI overstayed in terms of providing protection during arrest, detention, deportation and the rights of migrant workers who obtained a residence permit due to violation. In terms of the responsibility of the service user TKI / employer memnyebabkan TKI overstayed due to the attitude and actions of irresponsible form of detention document the service users migrant workers / employers should bear the risk and fulfill the rights of migrant workers who violated such as taking care of a residence permit / work a new one if workers will be work and take care of the return of migrant workers. However, if migrant workers overstayed not due to the employer's attitude and actions TKI service user / employer was not responsible. Therefore, the need for the parties in the placement of workers abroad, especially the representative of Indonesia to disseminate and efforts to raise awareness of the law for the perpetrators overstayed.